Study Of Various Agronomic Characters And Analysis Of Sor-gum (Sorghum Bicolor (L) Moench) Nira Content Local Vari-eties In Suspected Mutant By Gamma Irradiation - Pratama, Yusni Wahyu; Hazmi, Muhammad; Widiarti, Wiwit (Universitas Muhammadiyah Jember, 2024)
Sorghum is a cereal crop that has the potential to be developed, especially on marginal land because it has high adaptability. The importance of selecting the right sorghum variety is emphasised to achieve optimal production yields in Indonesia as each variety has unique characteristics, such as plant height, resistance to pests and diseases, and tolerance to land conditions. Other characteristics to consider are sugar content, flavour, and harvest time. The sugar content in sorghum juice can be used as a substitute for sugar and syrup in food, while the brix value is an indicator of the quality of the juice. The mutation method in plant breeding is one of the steps to produce sorghum varieties that are resistant to extreme environmental conditions. This study aimed to test the nira content in sorghum plants. The research was written using two components and factorial Randomised Group Design (RGD) with three replications, namely: The first factor was sorghum varieties Local Bandung (A0), Local Demak (A1), Local Jember (A2) while the second factor was gamma irradiation dose B0 (0 Gy), B1 (300 Gy), B2 (500 Gy) with a total of 135 plants. The results showed that the provision of some sorghum varieties and doses of gamma irradiation on the parameters of plant height, plant diameter, sucrose test analysis, fructose test analysis, glucose test analysis had a real and very real effect. The interaction of several varieties of sorghum and the dose of gamma-ray irradiation had a real and very real effect on the parameters of the number of leaves, sucrose test analysis, fructose test analysis, and glucose test analysis while for other parameters it had no real effect.